Mitochondrial P-JNK target, SAB (SH3BP5), in regulation of cell death - Win, Sanda; Than, Tin Aung; Kaplowitz, Neil (Frontiers in Cell and Developmental Biology, 2024)
Cell death occurs in various circumstances such as homeostasis, stress response, and defense, via specific pathways and mechanisms that are regulated by specific activator-induced signal transductions. Among them, JNKs participate in various aspects and the recent discovery of JNKs and mitochondrial protein SAB interaction in signal regulation of cell death completes our understanding of the mechanism of sustained activation of JNK (P-JNK) which leads to triggering the machinery of cell death. This understanding will lead the investigators to discover the modulators facilitating or preventing cell death for therapeutic application in acute or chronic diseases and cancer. We discuss here the mechanism and modulators of the JNK-SAB-ROS activation loop which is the core component of mitochondria-dependent cell death, specifically apoptosis and MTP-driven necrosis, and which may also contribute to cell death mechanisms of ferroptosis and pyroptosis. The discussion here is based on the results and evidence discovered from liver disease models but the JNK-SAB-ROS activation loop to sustain JNK activation is universally applicable to various disease models where mitochondria and ROS contribute to the mechanism of disease.